Heart Failure Duration Combined with Left Atrial Dimension Predicts Super-Response and Long-Term Prognosis in Patients with Cardiac Resynchronization Therapy Implantation. (24th June 2019) - Guo, Zhinian; Liu, Xiaoyan; Liu, Chuan; Yang, Jie; Cheng, Xiaofeng; Chen, Yunlong; Li, Ping; He, Yongming; Wang, Jiang
Abstract : Background . Response to cardiac resynchronization therapy (CRT) varies significantly among patients. This study aimed to identify baseline characteristics that could predict super-response to CRT and to evaluate the long-term prognosis in super-responders. Methods . We retrospectively reviewed the data of 73 consecutive patients who received CRT. Patients were considered as super-responders after 6-month follow-up when NYHA class reduction to I or II combined with left ventricular ejection fraction (LVEF) ≥ 50% was observed. Patients were divided into super-responders group and non-super-responders group. All-cause mortality or hospitalization for heart failure (HF) was referred to the combined end point. Results . 17 (23.3%) patients were super-responders. HF duration, left atrial dimension (LAD), and left bundle branch block (LBBB) were independent predictors of super-response to CRT. The combination of HF duration and LAD could provide more robust prediction of super-response than standalone HF duration (0.899 versus 0.789, Z = 2.207, P = 0.027) or standalone LAD (0.899 versus 0.775, Z = 2.487, P = 0.013). super-responders had excellent LV reverse remodeling. The cumulative incidences of combined end point were significantly lower in the super-responders group, LAD ≤ 42mm group, and combination of HF duration ≤ 48 months and LAD ≤ 42mm group. LBBB remained associated with a lowered risk of the combined end point (HR: 0.19, 95% CI: 0.07-0.57, P = 0.003), whereas LAD was associated with a raised risk of the combined end point (HR: 1.09, 95% CI: 1.02-1.17, P = 0.014). Conclusions . HF duration, LAD, and LBBB independently predicted super-response. The combination of HF duration and LAD makes more robust prediction of CRT super-response. Super-responders had excellent LV reverse remodeling and decreased the incidences of the combined end point. LBBB and LAD were independently associated with the combined end point.